Predictions of structure with soot concentration of propane-air turbulent-diffusion flames - 정종수; 신현동; 이춘식 (1988)
A modification of Tesner's two-step model for the rate of soot formation, with Samkhan's model for the spontaneous formation rate of radical nuclei from the fuel, has been tested on two propane/air turbulent-diffusion flames, to predict the soot concentration in flames. In order to evaluate the predictions, the new measurements of the mean soot-concentration field in a turbulent-jet propane/air diffusion flame are employed, along with data by Nishida. The proposed model gives fair predictions for soot concentration of two flames, and the soot formation rate in turbulent flames can be predicted simply by the application of a laminar-rate model and local time-mean conditions.